Low-temperature plasma as an approach for inhibiting a multi-species cariogenic biofilm - Figueira, Leandro W. [UNESP]; Panariello, Beatriz H. D.; Koga-Ito, Cristiane Y. [UNESP]; Duarte, Simone (MDPI, 2021)
This study aimed to determine how low-temperature plasma (LTP) treatment affects single-and multi-species biofilms formed by Streptococcus mutans, Streptococcus sanguinis, and Streptococcus gordonii formed on hydroxyapatite discs. LTP was produced by argon gas using the kIN-Pen09™ (Leibniz Institute for Plasma Science and Technology, INP, Greifswald, Germany). Biofilms were treated at a 10 mm distance from the nozzle of the plasma device to the surface of the biofilm per 30 s, 60 s, and 120 s. A 0.89% saline solution and a 0.12% chlorhexidine solution were used as negative and positive controls, respectively. Argon flow at three exposure times (30 s, 60 s, and 120 s) was also used as control. Biofilm viability was analyzed by colony-forming units (CFU) recovery and confocal laser scanning microscopy. Multispecies biofilms presented a reduction in viability (log10 CFU/mL) for all plasma-treated samples when compared to both positive and negative controls (p < 0.0001). In single-species biofilms formed by either S. mutans or S. sanguinis, a significant reduction in all exposure times was observed when compared to both positive and negative controls (p < 0.0001). For single-species biofilms formed by S. gordonii, the results indicate total elimination of S. gordonii for all exposure times. Low exposure times of LTP affects single-and multi-species cariogenic biofilms, which indicates that the treatment is a promising source for the development of new protocols for the control of dental caries.
Keywords: Antibacterial; Dental caries; Streptococcus gordonii; Streptococcus mutans; Streptococcus sanguinis